User requirements for national research and education networks for research in West and Central Africa. (September 2019) - Kashefi, Armin; Taylor, Simon JE; Abbott, Pamela; Anagnostou, Anastasia; Tessa, Ousmane Moussa; Oaiya, Omo; Barry, Boubakar; Alline, Damien
National research and education networks (NRENs) play a critical role in the development of communication network infrastructure and networked services for researchers and educators. They help close 'digital divides' between and within countries and are an essential factor for national and international development. In collaboration with the West and Central African Research and Education Network (WACREN), the TANDEM project has developed a roadmap for the development of NRENs in the region. This was based on the results of a survey that was conducted to investigate user requirements of networked services. The analysis of the 561 responses to a three-part questionnaire divided into 11 education, 22 research and 2 technical management questions identified key educational and research service needs. This article reports on the results of the survey with respect to research services. Highlights include respondents wanting regular access to online conference and academic articles (89%), a range of research services including online library resources, video conferencing, collaboration tools, online data access and storage, online library resources and inter-university login (>87%), access to remote computing facilities (80%) and high performance computing facilities (77%). A desire to share data with others online (74%) was also identified. Respondents also indicated that they would like to access research services through a range of device types–Laptops (96%), Fixed PC (86%) and Mobile Devices (81%). Poor network connectivity was consistently identified as being a major barrier to research in the region.